Interpersonal relationships between professionals and mothers of premature from Kangaroo-Unit - doi:10.5020/18061230.2010.p144 - Fabiane Elpidio de Sá; Raphael Colares de Sá; Lêda Maria da Frota Pinheiro; Francisca Eliene de Oliveira Callou (Universidade de Fortaleza, 2012)
Objective: To understand the interpersonal relationships between professionals and mothers of premature newborns of the Kangaroo Unit. Methods: This was an exploratory study of qualitative approach. The interviews were conducted with 10 mothers and 7 professionals who joined in Kangaroo Program and then analyzed by the content analysis technique. The guiding questions used were related to feelings perceived in relation to the Kangaroo method, related to mother-child dyad and interpersonal relationships. Results: Mothers reported on their speeches: "safe to be with the baby in Kangaroo Method" and "sense of maternal feeling during breastfeeding", while in the professionals' discourses have emerged: "guidelines on caring for the babies", "the embracement by the team" and "the importance of family support." Conclusions: The interaction between professionals and mothers of Kangaroo Unit facilitates the permanence of the binomial in the method, therefore develops feelings of security, tranquility and confidence to take care of the baby. It is important that the team be aware of the difficulties, supporting them in the weakest moments and sharing their fears, doubts and concerns over the baby's hospitalization.